148k views
0 votes
If m(x)=x2+3 and n(x) =5x+9 which expression is equivalent to (mn)(x)

User Landweber
by
5.2k points

2 Answers

4 votes

Answer:

A: 5
x^(3) + 9
x^(2) + 15x + 27

Explanation:

User Tjjjohnson
by
4.8k points
3 votes

Answer:

mn(x) = 5x³ + 9x² + 15x + 27

Explanation:

mn(x) = m(x) × n(x)

mn(x) = (x² + 3)(5x + 9)

We can evaluate this expression by using the FOIL method.

First terms: x² × 5x = 5x³

Outer terms: x² × 9 = +9x²

Inner terms: 3 × 5x = +15x

Last terms: 3 × 9 = +27

mn(x) = 5x³ + 9x² + 15x + 27

User Michiel Pater
by
5.6k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.